2022
DOI: 10.1186/s43141-022-00356-x
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of a new detergent-stable keratinase expressed by Pedobacter sp. 3.14.7, a novel Antarctic psychrotolerant keratin-degrading bacterium

Abstract: Background Antarctica is one of the harshest environments in the world. Despite this fact, it has been colonized by microorganisms, which had to develop different adaptations in order to survive. By studying their enzymes, we can harness these adaptations in order to use them in various industrial processes. Keratinases (E.C. 3.4.99.11) are characterized by their robustness in withstanding extreme conditions and, along with other enzymes, are commonly added to laundry detergents, which makes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 71 publications
1
10
0
Order By: Relevance
“…The protease retained 25%–40% of its activity in the presence of other laundry detergents, such as Ghadi, Fena, and Henko. The detergent‐compatible proteases from Bacillus had also shown compatibility with various laundry detergents, such as Ariel (Procter and Gamble), Henko (Henkel Spic India Limited), and Surf Excel (Hindustan Lever Limited) 42 , 47 49 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protease retained 25%–40% of its activity in the presence of other laundry detergents, such as Ghadi, Fena, and Henko. The detergent‐compatible proteases from Bacillus had also shown compatibility with various laundry detergents, such as Ariel (Procter and Gamble), Henko (Henkel Spic India Limited), and Surf Excel (Hindustan Lever Limited) 42 , 47 49 …”
Section: Resultsmentioning
confidence: 99%
“…The detergent-compatible proteases from Bacillus had also shown compatibility with various laundry detergents, such as Ariel (Procter and Gamble), Henko (Henkel Spic India Limited), and Surf Excel (Hindustan Lever Limited). 42,[47][48][49] 3.3.9…”
Section: Compatibility Of Proteases With Commercial Detergentmentioning
confidence: 99%
“…NFH5 1879.09 8.0 90 Metallo 39 This study Fervidobacterium islandicum AW-1 9 100 >200, 97 [ 58 ] Bacillus circulans DZ100 15,000 12.5 85 Serine 32 [ 59 ] Pedobacter sp. 3.14.7 33.04 7.5 55 Metallo 25 [ 61 ] Pseudomonas aeruginosa KS-1 1200 9 60 Serine 45 [ 62 ] Bacillus cereus YQ15 925 10 60 Serine-metallo [ 63 ] Acinetobacter sp. R-1 188 11 50 Metallo 25 [ 64 ] Chryseobacterium L99 sp.…”
Section: Discussionmentioning
confidence: 99%
“…Manonmani et al (2015) , reported in their study that keratinase enzyme obtained from Bacillus tropicus strain Gxun-17 has the highest activity at neutral pH close to alkaline. Rios et al (2022) investigated the Pedobacter sp. 3.14.7 strain among the 7 bacterial strains with keratinase activity isolated from Antarctic birds’ nests.…”
Section: Discussionmentioning
confidence: 99%